5/6*-1/5x+4=7/10x

Simple and best practice solution for 5/6*-1/5x+4=7/10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6*-1/5x+4=7/10x equation:


x in (-oo:+oo)

((-1*(5/6))/5)*x+4 = (7/10)*x // - (7/10)*x

((-1*(5/6))/5)*x-((7/10)*x)+4 = 0

((-5/6)/5)*x+(-7/10)*x+4 = 0

4-13/15*x = 0 // - 4

-13/15*x = -4 // : -13/15

x = -4/(-13/15)

x = 60/13

x = 60/13

See similar equations:

| 5x-41=3x-11 | | 0=-6x-4x+5 | | .8x+.5y=6597 | | (x+5)(x-5)-x(x-1)=0 | | 10x-5x-6-10x=7 | | 3(z+9)-(6z-9)=-4z | | 10/3-5=4/3x+7 | | 8+6x-4=9x+12-7x | | 7z-7=8z | | 25+17s=76 | | x/16=-8 | | -7-3=4x+7-3x | | x/25=-20+20 | | x-12=-29 | | 8-.5Q=1Q | | 8s=-72 | | 56*23-67/98*32= | | 7202-.23Q=.46Q | | 375-.25Q=.5Q | | 5.6q-5.3-5.2q=-0.6q-1.2 | | 9x-18+36/9x | | 24-0.10Q=.20Q | | 8x-6y=-96 | | x-8=-1+3 | | 5x+67=10x-13 | | 3x-12/x-2a+4/9 | | 12x+8-5=11x-2 | | 3y+2x=10 | | 3(y+2)+y=u(y-1)+10 | | 4g=-5s | | 31-3x=6x+16 | | t-45=-29 |

Equations solver categories